Patterns of fish and whale consumption in relation to methylmercury in hair among residents of Western Canadian Arctic communities - Emily V. Walker; Yan Yuan; Safwat Girgis; Karen J. Goodman (BMC, 2020)
Abstract Background Methylmercury contamination of the environment represents a substantial environmental health concern. Human exposure to methylmercury occurs primarily through consumption of fish and marine mammals. Heavily exposed subgroups include sport or subsistence fishers residing in Arctic communities. We aimed to estimate the association of fish/whale consumption patterns of Canadian Arctic subsistence fishers with the internal dose of methylmercury as measured in hair. Methods This research was conducted within ongoing community projects led by the CANHelp Working Group in Aklavik and Fort McPherson, Northwest Territories and Old Crow, Yukon. We interviewed each participant using a fish-focused food-frequency questionnaire during September-November 2016 and collected hair samples concurrently. Methylmercury was measured in the full-length of each hair sample using gas chromatography inductively-coupled plasma-mass spectrometry. Multivariable linear regression estimated beta-coefficients and 95% confidence intervals (CIs) for the effect of fish/whale consumption on hair-methylmercury concentrations. Results Among 101 participants who provided hair samples and diet data, the mean number of fish/whale species eaten was 3.5 (SD:1.9). The mean hair-methylmercury concentration was 0.60 μg/g (SD:0.47). Fish/whale consumption was positively associated with hair-methylmercury concentration, after adjusting for sex, hair length and use of permanent hair treatments. Hair-methylmercury concentrations among participants who consumed the most fish/whale in each season ranged from 0.30-0.50 μg/g higher than those who consumed < 1 meal/week. Conclusions In this population of Canadian Arctic subsistence fishers, hair-methylmercury concentration increased with fish/whale consumption, but the maximum concentrations were below Health Canada's 6.0 μg/g threshold for safe exposure.